Physical illness in looked-after children: a cross-sectional study. Issue 2 (6th August 2013) - Martin, Alice; Ford, Tamsin; Goodman, Robert; Meltzer, Howard; Logan, Stuart
Abstract : Objective: To compare the reported point prevalence of chronic physical illness among children looked after by local authorities with those living in their own homes. Design: Cross-sectional study, using questionnaire data from a national survey. Setting: The UK. Participants: Random samples of children aged 5–15 years. Children looked after were selected from Department of Health databases, stratified according to placement type. The child benefit register was the sampling frame for children in their own homes, weighted to match the child population demographic and compensate for response variability. Main outcome: Carer-reported prevalence of 10 physical illnesses. Results: Data were collected on 1253 looked-after children and 10 438 children in their own homes. There were lower rates of asthma, eczema and hay fever reported among looked-after children compared with children at home (ORs, adjusted for age, gender and ethnicity, were 0.63, 0.61 and 0.36, respectively). Epilepsy, cystic fibrosis and cerebral palsy were more commonly reported in looked-after children (adjusted ORs 4.13, 4.2 and 7.26, respectively). There was no difference in the proportions of children in the two groups reporting glue ear, diabetes mellitus, spina bifida or cancer. Conclusions: Looked-after children have an increased prevalence of some physical illnesses. The results also suggest that there may be significant unmet need, with health professionals and carers failing to identify other illnesses. The lower reported prevalence of atopic conditions may reflect a truly lower occurrence of such diseases in looked-after children; this requires further work to explore.